Wetlands as urban waste water treatment system - Suliman Bader, Ahmed; Mohamed Hezamalnadish, Adham; Essied Saied, Khalid; Albahlol Lih Swedi, Khaled; Ahmad Hussaini, Jagaba (Penerbit UTHM, 2020)
Wastewater treatment is a problem that has plagued human ever since the discoveries of discharging waste and wastewater into surface water can lead to many additional environmental problems. The Clean Water Act (P.L.92-500 passed in 1972 and its more recent amendments) led to the construction of new wastewater treatment facilities across the country to help control water pollution and other water related problems. Wetland system acts as cost effective and natural urban wastewater treatment. The aim of this study is to reveal the benefits of the wetland system and awareness of the local residents about the wetland system sustenance. The methods adopted in this study are identification of two development areas that possess a wetland, make a visit to the areas, interviews and distribution of questionnaire form, and analyse the results of the questionnaire. The Director PPH UTHM and the Architect of Pura Kencana together with a few residents from the two study areas were interviewed regarding the benefits and awareness level of people on wetland system, “Simple Random Sampling Method” was used to determine the number of people on which the questionnaire would be conducted at the two case study areas. Thirty (30) respondents from UTHM and twenty (20) respondents from Pura Kencana were involved in answering the questionnaires. Results from the questionnaires were analysed whether the community benefits from the wetland and their awareness level. Finally, recommendations to improve community awareness to ensure that the benefits of the wetlands are fully utilized were made.